2013
DOI: 10.4172/2329-6917.1000107
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of the Eph Receptor Family in Leukemia and Hematopoietic Malignancies: Prospects for Targeted Therapies

Abstract: There has been considerable interest in recent years in the development of therapies, which target Eph receptors or their ephrin ligands. The Eph receptor tyrosine kinases and their membrane bound ephrin ligands are cell surface molecules involved in many biological functions and cell behaviors during embryogenesis and in adult life. However, they are also expressed in an aberrant fashion on many tumors and are re-expressed on normal cells in nonmalignant pathological states. Some of the eph/ephrins including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…Expression of EphA3 in leukemia and the low expression on normal tissues led us to investigate the potential of EphA3 as a therapeutic target in ALL. 27 We showed that EphA3 was expressed in~1/3 of ALL cases and appears to be more significantly expressed in some subgroups, particularly cases having the t(1; 19) translocation. Although only four cases with MLL translocations were tested, taken together with our previous data, 28 it seems unlikely that EphA3 would be expressed in these leukemias as MLL transcriptionally induces expression of other Eph receptors with redundant function.…”
Section: Discussionmentioning
confidence: 74%
“…Expression of EphA3 in leukemia and the low expression on normal tissues led us to investigate the potential of EphA3 as a therapeutic target in ALL. 27 We showed that EphA3 was expressed in~1/3 of ALL cases and appears to be more significantly expressed in some subgroups, particularly cases having the t(1; 19) translocation. Although only four cases with MLL translocations were tested, taken together with our previous data, 28 it seems unlikely that EphA3 would be expressed in these leukemias as MLL transcriptionally induces expression of other Eph receptors with redundant function.…”
Section: Discussionmentioning
confidence: 74%
“…Eph receptors acting alone or with ephrin ligands play an important role in many pathological conditions, including cancer, which makes them potential therapeutic targets in a range of diseases [27]. Eph/ ephrin bidirectional signaling affects many important oncogenic pathways, including cell adhesion, invasion, migration, proliferation, and angiogenesis, through activation or inhibition of various signaling networks, including SRC family kinases; RAS/RHO family GTPases; Wnt/β-catenin; focal adhesion kinase (FAK); and the phosphoinositide 3-kinase/AKT (PI3K/ AKT), mitogen-activated protein kinase (MAPK), and vascular endothelial growth factor (VEGF) pathways [27,28].…”
Section: Use Of Eph Receptors As Mab Therapy In Hematological Malignamentioning
confidence: 99%
“…The expression of these genes has been implicated in mechanisms, including cell activation, adhesion, migration, and differentiation. Many studies have showed expression of the Eph/ephrin family of proteins on malignant hematopoietic cells [28,29]. Human EphA3 was first identified in a pre-B-ALL cell line and was subsequently shown to be expressed in a proportion of both lymphoid and myeloid leukemias [28][29][30][31][32].…”
Section: Use Of Eph Receptors As Mab Therapy In Hematological Malignamentioning
confidence: 99%
See 1 more Smart Citation
“…EphA3 expression has also been observed in multiple myeloma (De Vos et al, 2001) and can be induced by s-Thalidomide treatment in a myeloma cell line (Liu et al, 2004). Recently, EphA3 has been identified as a gene involved in survival of leukemic stem cells (Ashton et al, 2012) and therefore represents a new therapeutic target for hematologic malignancies (Charmsaz et al, 2013;Keane et al, 2012). Additionally, EphA3 expression in colorectal cancer (Xi, 2011), gastric cancer (Xi, 2012) glioblastoma (Day, 2013) and hepatocellular cancer (Lu et al, 2013) has been shown to correlate with poor prognosis.…”
Section: Introductionmentioning
confidence: 99%